Principal Investigators and R&D Failure Probability of Innovation Failure in Small Business - Boyce, Morgan (Cham : Springer International Publishing : Imprint: Springer, 2023)
Failure in R&D efforts are fairly common and with many factors that contribute to the outcome. This book focuses on the role of principal investigators (PIs) in R&D project failures and provides a theoretical model explaining how firm characteristics, including those of the PIs, impact the probability of failure. The theoretical model also serves as a structural form model to motivate the empirical analysis which assesses the probability of failure in small technology-based firms. The author uses data from the U.S. Department of Energy's (DOE) Small Business Innovation Research (SBIR) program to build a new and informative tool to assess R&D projects and demonstrate the strengths of the theoretical model. The association between PIs and R&D failure not only provides insights that can have a downstream impact to economic growth, but it can also provide policymakers with valuable information to aid decisions in allocating funds for R&D.
Introduction -- R&D Project Failure and Principal Investigators -- Part I : Contextual Setting -- Publicly Funded Collaborative R&D: The Case of the US Department of Energy -- Legislative History of The SBIR Program -- A Theoretical Model of R&D Project Success or Failure -- Department of Energy and SBIR Data -- Collaborative R&D Firm and Project Characteristics: Empirical Insights -- Principal Investigators Experience in Collaborative R&D: Empirical Findings -- Part II; Reflections And Future Perspectives -- PIs and R&D Project Failure: Reflections and Future Research Avenues.
Keywords: Technological innovations; Small business; Innovation and Technology Management; Economics of Innovation; Small Business